Legal Aid In Handling Cases Of Sexual Violence Against Children In Indonesia - Khulaili, Rabith Madah; Firmansyah, Firmansyah; Sari, Ade Risna; Widodo, Hadi; Salmon, Harly Clifford Jonas; Tinambunan, Hezron Sabar Rotua (Journal Of Human And Education (JAHE), 2025)
This community service was carried out for ten days in each village, including Kanci Kulon Village, Cirebon, Rejomulyo Metro Village, and Sabiyan Village, Bangkalan, Madura. The result in this article show the devotee has a formulation or summary in overcoming the problem of sexual violence against children that occurs in the village in stages, namely observing first whether the case that occurs is included in the category of sexual violence and is included in the category of sexual violence at what level, if it is true regardless of the level, it should be immediately reported to the village apparatus or other community leaders in order to get a solution immediately, the next stage is that both parents or guardians are called, and if no solution is found, the last solution is to report to the police. The author places reporting to the police at the last stage because the author understands that the legal solution is the ultimum remidium or the last weapon if other methods of resolution are no longer available. This stage is also intended to avoid unilateral mass judges